Digital Financial Inclusion and Economic Growth: Evidence from Emerging Economies Using Panel Data Analysis - Nurvita Sari Musdiani Silalahi (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
This study investigates the impact of digital financial inclusion on economic growth across emerging economies. With the rapid expansion of financial technologies, access to financial services has significantly improved, particularly in developing regions. However, empirical evidence regarding its macroeconomic effects remains inconclusive. This research employs panel data from 25 emerging economies spanning 2010–2023 and applies fixed effects and system Generalized Method of Moments (GMM) models to examine the relationship between digital financial inclusion and GDP growth. The findings reveal that digital financial inclusion significantly promotes economic growth by enhancing capital allocation efficiency, increasing savings, and supporting small and medium enterprises (SMEs). However, the results also indicate diminishing returns at higher levels of financial inclusion. Policy implications suggest that governments should focus not only on expanding access but also on improving financial literacy and regulatory frameworks to maximize the benefits of digital finance.